Pensijilan halal sebagai sekatan perdagangan bukan tarif: kajian kes Indonesia - Sunjay, Ariroza (2020)
The Halal certification in Indonesia is a unique mechanism. On the one hand, it can serve as a non-tariff barrier and yet on the other, it can also be utilized as a form of protection by the state to its people, especially the Muslim community on the matter concerning to food or medical consumption,. The study was conducted to achieve three main objectives. The first objective is to identify factors that would enable the implementation of Halal certification as one of the non-tariff barriers on imports to Indonesia. Secondly, to analyze the implementation of Halal certification procedures on imported food products to Indonesia. Thirdly, to determine the impact of the implementation of Halal certification in terms of advantages and disadvantages to Indonesian trade. This study utilized qualitative research methods, namely, interview and library studies. The findings of the study indicated that legal mandates, social and religious demands, and political factors related to Indonesia’s economy and its people are the key factors underlying the implementation of Halal certification in Indonesia. This research also found that disadvantages of the implementation of Halal Certification at the moment superseded the advantages. Therefore, this study proposes to the Indonesian government to strive to improve the quality of Halal certification so that it can benefit everyone in the near future.